Immunoinformatic exploration of a multi-epitope-based peptide vaccine candidate targeting emerging variants of SARS-CoV-2 - Kumar, K. M.; Karthik, Yalpi; Ramakrishna, D.; Balaji, S.; Skariyachan, Sinosh; Murthy, T. P. Krishna; Sakthivel, Kunnathur Murugesan; Alotaibi, Badriyah S.; Shukry, Mustafa; Sayed, Samy M.; Mushtaq, Muntazir (Frontiers in Microbiology, 2023)
Many countries in the world are severely suffering from the recently emerged variants of SARS-CoV-2. Over the last few months, scientists developing treatments, drugs, and vaccines to subside the pandemic and thus prevent its transmission. However, a peptide-based vaccine construct containing pathogenic proteins of the virus known to elicit an immune response was constructed. An analysis of the Spike protein-based epitopes allowed us to design an 'epitope-based subunit vaccine' against coronavirus using the approaches of 'reverse vaccinology' and 'immunoinformatics'. Computational experimentation and a systematic, comprehensive protocol were meant to develop and design a Multi-Epitope-Based Peptide (MEBP) vaccine candidate. Our study attempted to predict a MEBP vaccine by introducing mutations of SARS-CoV-2 (Delta, Lambda, Iota, Omicron and Kappa) in spike glycoprotein and predicting dual-purpose epitopes (B-cell and T-cell). This was followed by screening the selected epitopes based on antigenicity, allergenicity and population coverage and constructing them into a vaccine by using linkers and adjuvants. The vaccine construct was analyzed for its physicochemical properties, secondary structure prediction, and a 3D structure was built, refined, and validated. Further, the peptide-protein interaction of the vaccine construct with the Toll-like receptor (TLR) molecules was done. Immune profiling was done to check the immune response. Codon optimization of the vaccine construct was done to obtain the GC content to clone it into the E. coli genome to progress it into a vector. Finally, the In-silico simulation of the vaccine-protein complex was performed to comprehend the stability and conformational behavior.